PERSEPSI PESERTA DIDIK TENTANG KETERAMPILAN KOMUNIKASI GURU BK DALAM LAYANAN INFORMASI DI SMP NEGERI 20 PADANG - Ds, Bayu Marsha.; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
Problems studied the teacher providing counseling services counseling information monotonous because master class teacher, teacher counseling while providing less obvious questions so that the students could not answer. The purpose of this study: 1) Perception of students on communication skills in counseling teacher explains the material information services. 2) Perception of students on communication skills in providing counseling teacher question to students in the provision of information services. 3) Perception of students on communication skills in counseling teacher gives strength in the service information. This research is a descriptive study. The study population of students of SMP Negeri 20 Padang. Stratified sampling technique was rondom Sampling. Samples were taken from each class VIII and class IX through lottery. Number of samples 66 people. The research instrument was a questionnaire, data analysis techniques used percentages. The results in SMP Negeri 20 Padang in general is a very good. The results according to the lowest sub-variables, namely: 1) Describe the service material unfavorable category is 1.51%. 2) Asking the question in a category quite well with the percentage of 15.15%. 3) Provide reinforcement in the category quite well with the percentage of 16.66%. Based on the results of the study authors suggest counseling teacher further improve communication skills in the delivery of information services so that students can understand the material content of the service.